Knowledge and belief in Korean. (4th July 2022) - Turri, John; Park, YeounJun
ABSTRACT: Recent research has found that in the folk epistemology of American anglophones, knowledge does not entail belief. This runs contrary to a standard view in contemporary anglophone epistemology, according to which it is a conceptual truth that knowledge entails belief. In this paper, we investigate whether the conceptual dissociation between knowledge and belief is cross-culturally robust. Toward that end, we studied the judgments of Koreans. We found that the two principal findings from American folk epistemology replicate in Korean folk epistemology: Koreans displayed a central tendency to attribute knowledge without also attributing belief, and Koreans' knowledge attributions were not based on their belief attributions. Instead, according to our findings, when Koreans made judgments about knowledge and belief in the same context, their belief attributions were based on their knowledge attributions. Taken together, these findings advance understanding of cross-cultural philosophy and add to a growing list of cross-cultural similarities in human folk epistemology.